A rapid and robust translational model for testicular aging research - N. Schmid; Y. Stepanov; M. Offner; L. Scholz; C. Herrmann; S. Petkov; R. Behr; J. B. Stöckl; T. Fröhlich; A. Mayerhofer (Histochemistry and Cell Biology, 2026)
In humans, testicular peritubular cells (TPCs) form a small compartment surrounding the seminiferous tubules and, as shown previously, undergo age-related changes. How they may contribute to the age-associated decline of testicular functions is not well known. Likewise, the mechanisms of testicular aging in humans are not well examined. This is in part due to the lack of appropriate cellular models. We aimed to establish an aging model of TPCs, which is based on immortalized nonhuman primate (NHP) peritubular cells (iMKTPCs) from Callithrix jacchus . As shown previously by a comprehensive proteomic approach, they strongly resemble human TPCs but lack the human cell-intrinsic heterogeneity. Cellular senescence was robustly induced within 10 days upon exposure to 25 µg/mL bleomycin for 24 h. This resulted in increased β-galactosidase activity, enlarged cells, and elevated transcript levels of senescence-associated secretory phenotype (SASP) molecules ( IL1b , TNFa , CCL2 ). The ability to contract upon a stimulus was reduced, as shown in live cell imaging studies. Reduced proliferation among others was indicated by a decreased abundance of proliferating cell nuclear antigen (PCNA), evident in a proteomic analysis, which also revealed massive changes (341 significantly increased and 372 decreased proteins). Bioinformatics analysis indicated a marked reduction in several cell-motility–associated proteins, whereas proteins linked to extracellular exosomes, the cytoskeleton, and lysosomal pathways were increased in abundance. To conclude, bleomycin treatment causes a rapid and robust induction of cellular senescence in a translational testicular cell model of peritubular cells. This model will enable future studies aiming to explore mechanisms and consequences of testicular aging.

Beyond mobility: A prospective study on diet and metabolism in hereditary spastic paraplegia - Christina Erhardt; Imke T. Spatz; Hans J. Herrmann; Zacharias Kohl; Yurdagül Zopf; Heiko Gassner; Jürgen Winkler; Martin Regensburger (Metabolic Brain Disease, 2026)
Metabolism plays an important role in neurodegenerative diseases. Hereditary spastic paraplegias (HSP) are a heterogeneous group of rare genetic neurodegenerative disorders, commonly characterized by the clinical syndrome of progressive lower limb spasticity and mobility loss. Obesity has been linked to distinct genotypes, but the role of metabolism and nutrition in HSP remains unclear.We aimed to To evaluate metabolism and nutrition in specific HSP genotypes and to assess the impact of nutritional counseling on disease progression and body composition. In this prospective explorative pilot study, we assessed the neurological, metabolic and nutritional status of patients with HSP at baseline and one year after nutritional counseling. A total of 36 patients with genetically confirmed SPG4-, SPG7- and SPG11-associated HSP were recruited. BMI in SPG4 and SPG7 was comparable to healthy population data, whereas SPG11 showed significantly higher BMI (+ 22.9%, p < 0.05) with a considerable interindividual variability. Across all genotypes, disease severity according to the Spastic Paraplegia Rating Scale correlated negatively with leg muscle mass (ρ = -0.39, p < 0.05), protein (ρ = -0.35, p < 0.05) and fiber intake (ρ = -0.41, p < 0.05). After one year, there was a significant loss of relative muscle mass (-7.2%, p < 0.001). Progressive loss of muscle mass in HSP asks for an effective nutritional intervention combined with exercise in order to influence disease progression in HSP. The SPG11-associated obese phenotype may evolve with disease progression due to multifactorial metabolic changes, beyond reduced mobility.

Pre- and post-harvest spectral estimation of carnosic acid and rosmarinic acid in rosemary - A. Mishra; A. Krief; M.M. Sahoo; A. Schachter; I. Gonda; N. Dudai; T. Trigano; I. Herrmann (Computers and Electronics in Agriculture, 2026)

Factors affecting 87Sr/86Sr preservation in conodont apatite: An example from the Ordovician of Baltoscandia - Christopher T. Conwell; Matthew R. Saltzman; Anders Lindskog; Mats E. Eriksson; Elizabeth M. Griffith; Stephen A. Leslie; Cole T. Edwards; Olle Hints; Achim D. Herrmann (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Performance of a green wall in treating organics, nutrients and pathogens in greywater in a cool climate - Mashreki Sami; Annelie Hedström; Elisabeth Kvarnström; David T. McCarthy; Heinz Gattringer; Marco Hartl; Inga Herrmann (Journal of Water Process Engineering, 2026)

Hard-seeded annual pasture legume phases are a profitable and low risk option in mixed farming regions with low to medium rainfall - Dean T. Thomas; Sadeeka L. Jayasinghe; Chris Herrmann; Robert J. Harrison; Bonnie M. Flohr; Roger A. Lawes (Agricultural Systems, 2025)

Rapid subsidence as a driver of phosphate deposition in the later Ordovician: Case study from the Alabama Appalachians - John T. Haynes; Rafael A. Villanueva; Richard M. Robinet; Stephen A. Leslie; Achim D. Herrmann (Sedimentary Geology, 2025)

Crossing the Pacific: Genomics Reveals the Presence of Japanese Sardine ( Sardinops melanosticta ) in the California Current Large Marine Ecosystem - Gary C. Longo; Jeremiah J. Minich; Nicholas Allsing; Kelsey James; Ella S. Adams‐Herrmann; Wes Larson; Nolan Hartwick; Tiffany Duong; Barbara Muhling; Todd P. Michael; Matthew T. Craig (Molecular Ecology, 2024)
Recent increases in frequency and intensity of warm water anomalies and marine heatwaves have led to shifts in species ranges and assemblages. Genomic tools can be instrumental in detecting such shifts. In the early stages of a project assessing population genetic structure in Pacific Sardine ( Sardinops sagax ), we detected the presence of Japanese Sardine ( Sardinops melanosticta ) along the west coast of North America for the first time. We assembled a high quality, chromosome‐scale reference genome of the Pacific Sardine and generated low coverage, whole genome sequence (lcWGS) data for 345 sardine collected in the California Current Large Marine Ecosystem (CCLME) in 2021 and 2022. Fifty individuals sampled in 2022 were identified as Japanese Sardine based on strong differentiation observed in lcWGS SNP and full mitogenome data. Although we detected a single case of mitochondrial introgression, we did not observe evidence for recent hybridization events. These findings change our understanding of Sardinops spp. distribution and dispersal in the Pacific and highlight the importance of long‐term monitoring programs.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

Local fractal dimension of collagen detects increased spatial complexity in fibrosis - Dylan T. Casey; Karolyn G. Lahue; Vitor Mori; Jacob Herrmann; Joseph K. Hall; Béla Suki; Yvonne M. W. Janssen-Heininger; Jason H. T. Bates (Histochemistry and Cell Biology, 2024)
Increase of collagen content and reorganization characterizes fibrosis but quantifying the latter remains challenging. Spatially complex structures are often analyzed via the fractal dimension; however, established methods for calculating this quantity either provide a single dimension for an entire object or a spatially distributed dimension that only considers binary images. These neglect valuable information related to collagen density in images of fibrotic tissue. We sought to develop a fractal analysis that can be applied to 3-dimensional (3D) images of fibrotic tissue. A fractal dimension map for each image was calculated by determining a single fractal dimension for a small area surrounding each image pixel, using fiber thickness as the third dimension. We found that this local fractal dimension increased with age and with progression of fibrosis regardless of collagen content. Our new method of distributed 3D fractal analysis can thus distinguish between changes in collagen content and organization induced by fibrosis.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Long-Term Impacts of Invasive Insects and Pathogens on Composition, Biomass, and Diversity of Forests in Virginia’s Blue Ridge Mountains - Kristina J. Anderson-Teixeira; Valentine Herrmann; Wendy B. Cass; Alan B. Williams; Stephen J. Paull; Erika B. Gonzalez-Akre; Ryan Helcoski; Alan J. Tepley; Norman A. Bourg; Christopher T. Cosma; Abigail E. Ferson; Caroline Kittle; et al. (Ecosystems, 2021)

Genome‐inferred spatio‐temporal resolution of an uncultivated Roizmanbacterium reveals its ecological preferences in groundwater - Patricia Geesink; Carl‐Eric Wegner; Alexander J. Probst; Martina Herrmann; Hang T. Dam; Anne‐Kristin Kaster; Kirsten Küsel (Environmental Microbiology, 2020)
Summary Subsurface ecosystems like groundwater harbour diverse microbial communities, including small‐sized, putatively symbiotic organisms of the Candidate Phyla Radiation, yet little is known about their ecological preferences and potential microbial partners. Here, we investigated a member of the superphylum Microgenomates ( Cand . Roizmanbacterium ADI133) from oligotrophic groundwater using mini‐metagenomics and monitored its spatio‐temporal distribution using 16S rRNA gene analyses. A Roizmanbacteria‐specific quantitative PCR assay allowed us to track its abundance over the course of 1 year within eight groundwater wells along a 5.4 km hillslope transect, where Roizmanbacteria reached maximum relative abundances of 2.3%. In‐depth genomic analyses suggested that Cand . Roizmanbacterium ADI133 is a lactic acid fermenter, potentially able to utilize a range of complex carbon substrates, including cellulose. We hypothesize that it attaches to host cells using a trimeric autotransporter adhesin and inhibits their cell wall biosynthesis using a toxin–antitoxin system. Network analyses based on correlating Cand . Roizmanbacterium ADI133 abundances with amplicon sequencing‐derived microbial community profiles suggested one potential host organism, classified as a member of the class Thermodesulfovibrionia (Nitrospirae). By providing lactate as an electron donor Cand . Roizmanbacterium ADI133 potentially mediates the transfer of carbon to other microorganisms and thereby is an important connector in the microbial community.

Soluble Epoxide Hydrolase-Derived Linoleic Acid Oxylipins in Serum Are Associated with Periventricular White Matter Hyperintensities and Vascular Cognitive Impairment - Di Yu; Marie Hennebelle; Demetrios J. Sahlas; Joel Ramirez; Fuqiang Gao; Mario Masellis; Hugo Cogo-Moreira; Richard H. Swartz; Nathan Herrmann; Pak Cheung Chan; Jacqueline A. Pettersen; Donald T. Stuss; et al. (Translational Stroke Research, 2019)

Allelic nomenclature for the duplicated MHC class II DQ genes in sheep - Keith T. Ballingall; Kara Dicks; Panoraia Kyriazopoulou; Lynne Herrmann-Hoesing (Immunogenetics, 2019)

Prolonged suppressive antibiotic therapy for prosthetic joint infection in the elderly: a national multicentre cohort study - V. Prendki; T. Ferry; P. Sergent; E. Oziol; E. Forestier; T. Fraisse; S. Tounes; S. Ansart; J. Gaillat; S. Bayle; O. Ruyer; F. Borlot; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Prevalence of K65R in patients treated with tenofovir disoproxil fumarate: recommendations based on the Frankfurt HIV Cohort Study Resistance Database (FHCS-RD) - Claudia Reinheimer; Anna Wesner; Oliver T. Keppler; Hans Wilhelm Doerr; Eva Herrmann; Martin Stürmer; Christoph Stephan (Medical Microbiology and Immunology, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Semiautomated quantitative image analysis of glomerular immunohistochemistry markers desmin, vimentin, podocin, synaptopodin and WT-1 in acute and chronic rat kidney disease models - J. Funk; V. Ott; A. Herrmann; W. Rapp; S. Raab; W. Riboulet; A. Vandjour; E. Hainaut; A. Benardeau; T. Singer; B. Jacobsen (Histochemistry and Cell Biology, 2016)

Accumulation of Traffic-Related Trace Metals in Urban Winter-Long Roadside Snowbanks - S. Moghadas; K. H. Paus; T. M. Muthanna; I. Herrmann; J. Marsalek; M. Viklander (Water, Air, & Soil Pollution, 2015)

Analysing the effect of soil organic matter on bacterial communities using T-RFLP fingerprinting: different methods, different stories? - A. Blaud; F. Diouf; A. M. Herrmann; T. Z. Lerch (Biology and Fertility of Soils, 2015)

miR-375 gene dosage in pancreatic β-cells: implications for regulation of β-cell mass and biomarker development - Mathieu Latreille; Karolin Herrmanns; Neil Renwick; Thomas Tuschl; Maciej T. Malecki; Mark I. McCarthy; Katharine R. Owen; Thomas Rülicke; Markus Stoffel (Journal of Molecular Medicine, 2015)

Chemical properties of HULIS from three different environments - T. B. Kristensen; L. Du; Q. T. Nguyen; J. K. Nøjgaard; C. Bender Koch; O. Faurskov Nielsen; A. G. Hallar; D. H. Lowenthal; B. Nekat; D. van Pinxteren; H. Herrmann; M. Glasius; et al. (Journal of Atmospheric Chemistry, 2015)

Confronting Uncertainty in Life Cycle Assessment Used for Decision Support - Ivan T. Herrmann; Michael Z. Hauschild; Michael D. Sohn; Thomas E. McKone (Journal of Industrial Ecology, 2014)
Summary The aim of this article is to help confront uncertainty in life cycle assessments (LCAs) used for decision support. LCAs offer a quantitative approach to assess environmental effects of products, technologies, and services and are conducted by an LCA practitioner or analyst (AN) to support the decision maker (DM) in making the best possible choice for the environment. At present, some DMs do not trust the LCA to be a reliable decision‐support tool—often because DMs consider the uncertainty of an LCA to be too large. The standard evaluation of uncertainty in LCAs is an ex‐post approach that can be described as a variance simulation based on individual data points used in an LCA. This article develops and proposes a taxonomy for LCAs based on extensive research in the LCA, management, and economic literature. This taxonomy can be used ex ante to support planning and communication between an AN and DM regarding which type of LCA study to employ for the decision context at hand. This taxonomy enables the derivation of an LCA classification matrix to clearly identify and communicate the type of a given LCA. By relating the LCA classification matrix to statistical principles, we can also rank the different types of LCA on an expected inherent uncertainty scale that can be used to confront and address potential uncertainty. However, this article does not attempt to offer a quantitative approach for assessing uncertainty in LCAs used for decision support.

Enabling optimization in LCA: from “ad hoc” to “structural” LCA approach—based on a biodiesel well-to-wheel case study - Ivan T. Herrmann; Martin Lundberg-Jensen; Andreas Jørgensen; Thomas Stidsen; Henrik Spliid; Michael Hauschild (The International Journal of Life Cycle Assessment, 2014)

Analysis of the link between a definition of sustainability and the life cycle methodologies - Andreas Jørgensen; Ivan T. Herrmann; Anders Bjørn (The International Journal of Life Cycle Assessment, 2013)

Longitudinal Dispersion Coefficient: Effects of Particle-Size Distribution - Amir Jourak; Vilnis Frishfelds; J. Gunnar I. Hellström; T. Staffan Lundström; Inga Herrmann; Annelie Hedström (Transport in Porous Media, 2013)

Potential for optimized production and use of rapeseed biodiesel. Based on a comprehensive real-time LCA case study in Denmark with multiple pathways - Ivan T. Herrmann; Andreas Jørgensen; Sander Bruun; Michael Z. Hauschild (The International Journal of Life Cycle Assessment, 2013)

Migration as an escape from parasitism in New Zealand galaxiid fishes - Robert Poulin; Gerard P. Closs; Adrian W. T. Lill; Andy S. Hicks; Kristin K. Herrmann; David W. Kelly (Oecologia, 2012)

Size-segregated characterization of PM10 at the EMEP site Melpitz (Germany) using a five-stage impactor: a six year study - G. Spindler; T. Gnauk; A. Grüner; Y. Iinuma; K. Müller; S. Scheinhardt; H. Herrmann (Journal of Atmospheric Chemistry, 2012)

A study to discriminate local, urban and regional source contributions to the particulate matter concentrations in the city of Dresden, Germany - T. Gnauk; K. Müller; E. Brüggemann; W. Birmili; K. Weinhold; D. van Pinxteren; G. Löschau; G. Spindler; H. Herrmann (Journal of Atmospheric Chemistry, 2011)

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

Inefficient clearance of dying cells in patients with SLE: anti-dsDNA autoantibodies, MFG-E8, HMGB-1 and other players - Kristin Kruse; Christina Janko; Vilma Urbonaviciute; Claudia T. Mierke; Thomas H. Winkler; Reinhard E. Voll; Georg Schett; Luis E. Muñoz; Martin Herrmann (Apoptosis, 2010)

Resonance phenomena in the human auditory cortex: individual resonance frequencies of the cerebral cortex determine electrophysiological responses - T. Zaehle; D. Lenz; F. W. Ohl; C. S. Herrmann (Experimental Brain Research, 2010)

Incomplete nonsense-mediated decay of mutant lamin A/C mRNA provokes dilated cardiomyopathy and ventricular tachycardia - Stephanie K. Geiger; Harald Bär; Philipp Ehlermann; Sarah Wälde; Désirée Rutschow; Raphael Zeller; Boris T. Ivandic; Hanswalter Zentgraf; Hugo A. Katus; Harald Herrmann; Dieter Weichenhan (Journal of Molecular Medicine, 2008)

Vectorial transport of the plant alkaloid berberine by double-transfected cells expressing the human organic cation transporter 1 (OCT1, SLC22A1) and the efflux pump MDR1 P-glycoprotein (ABCB1) - Anne T. Nies; Elke Herrmann; Manuela Brom; Dietrich Keppler (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

A source study of PM in Saxony by Size-Segregated Characterisation - H. Herrmann; E. Brüggemann; U. Franck; T. Gnauk; G. Löschau; K. Müller; A. Plewka; G. Spindler (Journal of Atmospheric Chemistry, 2006)

Calcium Tartrate Crystals in the Midgut of the Grape Leafhopper - S. Böll; T. Schmitt; C. Burschka; P. Schreier; P. Schwappach; J. V. Herrmann (Journal of Chemical Ecology, 2005)

Size-Resolved Aerosol Characterization for a Polluted Episode at the IfT Research Station Melpitz in Autumn 1997 - A. Plewka; T. Gnauk; E. Brüggemann; C. Neusüss; H. Herrmann (Journal of Atmospheric Chemistry, 2004)

Treatment of Severe Candida Infections in High-Risk Patients in Germany: Consensus Formed by a Panel of Interdisciplinary Investigators - Büchner T.; Fegeler W.; Bernhardt H.; Brockmeyer N.; Duswald K.-H.; Herrmann M.; Heuser D.; Jehn U.; Just-Nübling G.; Karthaus M.; Maschmeyer G.; Müller F.-M.; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Role of apoptosis in autoimmunity - H-M. Lorenz; M. Herrmann; T. Winkler; U. Gaipl; J. R. Kalden (Apoptosis, 2000)

A polymorphism of the rat T-cell receptor β-chain variable gene 13 ( BV13S1 ) correlates with the frequency of BV13S1-positive CD4 cells - M. Stienekemeier; K. Hofmann; R. Gold; T. Herrmann (Immunogenetics, 2000)

Analysis of single-nucleotide polymorphisms in the interleukin-4 receptor gene for association with inflammatory bowel disease - M. Olavesen; J. Hampe; M. M. Mirza; R. Saiz; C. M. Lewis; S. Bridger; D. Teare; D. F. Easton; T. Herrmann; G. Scott; J. Hirst; J. Sanderson; et al. (Immunogenetics, 2000)

Amplification of Y-chromosomal STRs from ancient skeletal material - T. Schultes; Susanne Hummel; Bernd Herrmann (Human Genetics, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Time behavior of topological ordering in self-organizing feature mapping - R. Der; M. Herrmann; T. Villmann (Biological Cybernetics, 1997)